Caregiver self‐efficacy and associated factors among caregivers of patients with dementia with Lewy bodies and caregivers of patients with Alzheimer's disease. Issue 5 (3rd July 2021) - Sato, Hirofumi; Nakaaki, Shutaro; Sato, Junko; Shikimoto, Ryo; Furukawa, Toshi A.; Mimura, Masaru; Akechi, Tatsuo
Abstract: Background: Dementia with Lewy bodies (DLB) is characterized by neuropsychiatric symptoms, which can be distressing to caregivers. However, little is known about their subjective distress in terms of caregiver self‐efficacy. Thus, we examined the differences in caregiver self‐efficacy and their associated factors between DLB and Alzheimer's disease (AD) caregivers. Methods: We conducted a comprehensive questionnaire for DLB and AD caregivers. Caregiver self‐efficacy was evaluated using three domains (Self‐Efficacy for Obtaining Respite: SE‐OR, Self‐Efficacy for Responding to Disruptive Patient Behaviours: SE‐RDPB, Self‐Efficacy for Controlling Upsetting Thoughts about Caregiving: SE‐CUT) of the Revised Scale for Caregiving Self‐Efficacy (RSCSE). In addition, data on the following features of caregivers were assessed: depression, sleep disturbance, caregiver burden, executive function, loneliness, social support, and distress associated with neuropsychiatric symptoms. The patients were assessed for general cognitive tasks, executive function, and neuropsychiatric symptoms. Results: Compared with AD caregivers, DLB caregivers experienced a significantly higher burden in terms of not only various clinical factors, but also all three domains of caregiver self‐efficacy. Among the caregiver‐associated factors, different domains were predictors of self‐efficacy in DLB and AD caregivers (distress due to sleep disturbances in DLB patients; distress due to delusions in AD patients). Among the patient‐associated factors, different domains were also predictors of self‐efficacy in DLB and AD caregivers (sleep disturbances in DLB patients; delusions in AD patients). Among both the caregivers and the patients, executive function was a significant predictor of one RSCSE domain (SE‐CUT). Conclusions: A reduction in caregiver self‐efficacy may contribute to a severe subjective burden among DLB caregivers. Furthermore, two neuropsychiatric symptoms (delusions and sleep disturbances) affected caregiver self‐efficacy differently depending on whether care was being provided to a DLB or AD patient. Understanding the association between specific neuropsychiatric symptoms and caregiver self‐efficacy may be useful for conducting interventions for DLB patients.